TYPES OF INVENTIVE ABILITIES IN STUDENTS AND THEIR COVERAGE IN THE SUBJECT "TECHNOLOGY" - Yangibayeva Qunduzoy (Web of Journals Publishing, 2025)
In this article the types of inventive abilities in students, the factors of their formation and the methods of developing these abilities within the framework of modern discipline "Technology" are analyzed on a scientific basis. The results of research conducted on the basis of IMRAD requirements, the role of the subject "Technology" in the formation of students' creativity and problem-thinking skills, as well as the ways of their effective illumination through modern teaching technologies.
Keywords: Inventiveness, creativity, technology science, methodology, innovation, reader ability.